The Jadid Theater and Ethnic Traditions - Botir Sangirov (International Journal Of Literature And Languages, 2025)
This article explores the development of the Jadid theater as a significant cultural phenomenon in the early 20th century, particularly in Central Asia. The study analyzes how Jadid reformers utilized theater as a medium for enlightenment and modernization while incorporating local ethnic traditions and folklore to ensure cultural continuity. The research examines theatrical performances, scripts, and staging practices to highlight how Jadid theater served both pedagogical and national purposes. It also addresses the tension between traditional performance elements and modern dramaturgical innovations introduced by Jadid intellectuals. The findings underscore the role of the Jadid theater in shaping national identity, fostering social reform, and preserving ethnic cultural values through performative expression.